Functional complementation and genetic deletion studies of KirBac channels: Activatory mutations highlight gating-sensitive domains - Paynter, J; Andres-Enguix, I; Fowler, P; Tottey, S; Cheng, W; Enkvetchakul, D; Bavro, V; Kusakabe, Y; Sansom, M; Robinson, N; Nichols, C; Tucker, S (2010)
The superfamily of prokaryotic inwardly rectifying (KirBac) potassium channels is homologous to mammalian Kir channels. However, relatively little is known about their regulation or about their physiological role in vivo. In this study, we have used random mutagenesis and genetic complementation in K +-auxotrophic Escherichia coli and Saccharomyces cerevisiae to identify activatory mutations in a range of different KirBac channels. We also show that the KirBac6.1 gene (slr5078) is necessary for normal growth of the cyanobacterium Synechocystis PCC6803. Functional analysis and molecular dynamics simulations of selected activatory mutations identified regions within the slide helix, transmembrane helices, and C terminus that function as important regulators of KirBac channel activity, as well as a region close to the selectivity filter of KirBac3.1 that may have an effect on gating. In particular, the mutations identified in TM2 favor a model of KirBac channel gating in which opening of the pore at the helix-bundle crossing plays a far more important role than has recently been proposed. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.